Investigation of vibration dynamics in vertical plane of tractors with single and doubled wheels - Bulgakov, Volodymyr; Булгаков, Володимир Михайлович; Adamchuk, Valerii; Адамчук, Валерій Васильович; Antoshchenkov, Roman; Holovach, Ivan; Головач, Іван Володимирович; Rucins, Adolfs; Aboltins, Aivars; Beloev, Ivan; Halych, Ivan; Trokhaniak, Oleksandra; et al. (Jelgava, 2025)
The article presents the results of investigation of the dynamics of single and double-wheeled tractor systems in a vertical direction depending on the profile of the supporting surface. The study was conducted for tractors of the HTZ-240 series. It has been established that an increase in the efficiency and productivity of the machine and tractor aggregates is achieved by increasing the operating speeds, processing width and rational use of equipment. However, the uneven field surfaces and travel speeds cause additional vibrations that negatively affect the performance of the aggregates and can lead to increased soil compaction. To understand this process better, a mathematical model of the wheel has been developed that takes into account the rolling resistance coefficient, which depends on the pressure in the tyres, and on the speed. An equivalent dynamic model of single- and double-wheeled systems was also compiled in the MatLab/Simulink environment. Parameters of oscillations of the wheel system have been determined: the minimum radius of a single wheel is 0.7599 m, the maximum is 0.8605 m, and the span is 0.1006 m; for a doubled wheel, the minimum radius is 0.75 m, the maximum is 0.820 m, and the span is 0.07 m. Doubled wheel demonstrates a smaller amplitude and span of vertical oscillations, as well as a more stable dynamic radius, compared to the single wheel system. A conclusion has been drawn that the obtained results may be used to improve the designs of the tractor wheel systems in order to improve their performance characteristics and reduce the negative impact on the soil.
Keywords: dynamics; wheel; tractor; slippage; speed; dynamic radius